Assessment of the investment attractiveness of the regional economic sectors on the example of the Kirov region - E. N. Nagovitsyna (Publishing House of the State University of Management, 2021)
The article focuses on the fact that the general struggle for investment resources, both at the state level and at the regional level, forces us to study the essence, content of the investment process, the forms of interaction between its participants in more depth and in detail, assess the investment potential of individual sectors of the economy and look for ways to improve its efficiency. When studying the investment attractiveness of economic sectors, such a methodology was used, which includes three stages: 1) assessment of the socio-economic situation of the region and determination of its rating in Russia; 2) analysis of the dynamics and structure of investments in fixed assets; 3) identification of benefits that provide investment incentives for external investors in the regional system and deter conditions for the development of investment activity. It has been revealed that there is a significant gap between regions in terms of investment activity in the Russian economy, which contradicts the principle of a single economic space of the country. The Kirov region is analysed in relation to other regions of the country in terms of the indicators under consideration. The most attractive sectors of the region’s economy for investors have been identified. The article shows how important it is to assess the investment attractiveness of individual sectors of the economy of the Kirov region in order to offer the most profitable investment projects in the future.